2014
DOI: 10.3748/wjg.v20.i1.163
|View full text |Cite
|
Sign up to set email alerts
|

Serum and urine metabolomic fingerprinting in diagnostics of inflammatory bowel diseases

Abstract: NMR-based metabolomic fingerprinting of serum and urine has the potential to be a useful tool in distinguishing patients with active IBD from those in remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
144
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(162 citation statements)
references
References 56 publications
17
144
1
Order By: Relevance
“…Then, we should clarify whether partial inhibition is clinically relevant effect in animal models. 22) It has been reported that serum amino acid concentration of IBD patients was significantly high when compared to health volunteers, 23,24) which is consistent with the increased expression level of PEPT1 in IBD patients. Furthermore, serum amino acid concentrations were lower in IBD patients in remission status than in IBD active patients.…”
Section: -17)supporting
confidence: 60%
See 1 more Smart Citation
“…Then, we should clarify whether partial inhibition is clinically relevant effect in animal models. 22) It has been reported that serum amino acid concentration of IBD patients was significantly high when compared to health volunteers, 23,24) which is consistent with the increased expression level of PEPT1 in IBD patients. Furthermore, serum amino acid concentrations were lower in IBD patients in remission status than in IBD active patients.…”
Section: -17)supporting
confidence: 60%
“…Furthermore, serum amino acid concentrations were lower in IBD patients in remission status than in IBD active patients. 24) Thus, the inhibition for PEPT1 could be useful to improve the clinical effect by reducing the absorption of causative substances such as bacterial peptide from the intestine.…”
Section: -17)mentioning
confidence: 99%
“…Urinary metabolite profiling allowed to differentiate between UC and CD in only 1 study [40] , whereas 3 other studies failed to do so [41][42][43] . Also for serum metabolomics, discrimination between CD and UC was less pronounced with only 2 studies that were able to separate between patient subtypes.…”
Section: Differentiation Of Ibd Subtypesmentioning
confidence: 99%
“…Besides fecal metabolite profiling, urine profiling can be performed as many microbial metabolites are absorbed from the colonic lumen and excreted in urine, either as such or after further processing by human enzymes. Several studies were able to discriminate IBD patients from HCs based on metabolite profiling of urine samples [40][41][42][43] , but not all [44] . Also, amino acids and amino acid-derived metabolites were found as discriminating compounds in urine.…”
Section: Ibd Disease Signature: Case-control Studiesmentioning
confidence: 99%
See 1 more Smart Citation